Attachment to God/Higher Power and Bulimic Symptoms Among College Women. Issue 2 (1st July 2016) - Buser, Juleen K.; Gibson, Sandy
Abstract : The authors examined the relationship between avoidant and anxious attachment to God/Higher Power and bulimia symptoms among 599 female college student participants. After controlling for body mass index, the authors found a positive association between both attachment variables and bulimia. When entered together in a regression, anxious attachment to God/Higher Power had a stronger relationship with bulimia than did avoidant attachment to God/Higher Power. The authors discuss implications for college counseling.